2003
DOI: 10.1029/2002jb002055
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum in magnesium silicate perovskite: Formation, structure, and energetics of magnesium‐rich defect solid solutions

Abstract: [1] MgSiO 3 -rich perovskite is expected to dominate Earth's lower mantle (pressures >25 GPa) with iron and aluminum as significant substituents. The incorporation of trivalent ions, M 3+ , may occur by two competing mechanisms: Mg A + Si B = M A + M B and Si B = Al B + 0.5 (vacancy) O . Phase synthesis studies show that both substitutions do occur and the nonstoichiometric or defect substitution is prevalent along the MgSiO 3 -MgAlO 2.5 join. Lattice parameters associated with the first substitution (stoichio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…At 27 GPa, the number of oxygens in bridgmanite for the En 90 Brm 10 composition is 2.973 ± 0.004, which is slightly lower than those in Navrotsky et al (2003) and Kojitani et al (2007) and substantially lower than that of En 95 Cor 5 bridgmanite. This value shows clearly the presence of oxygen vacancies as consistent with 27 Al NMR observations by Stebbins et al (2003).…”
Section: Geochemical Perspectives Letters Lettermentioning
confidence: 99%
See 2 more Smart Citations
“…At 27 GPa, the number of oxygens in bridgmanite for the En 90 Brm 10 composition is 2.973 ± 0.004, which is slightly lower than those in Navrotsky et al (2003) and Kojitani et al (2007) and substantially lower than that of En 95 Cor 5 bridgmanite. This value shows clearly the presence of oxygen vacancies as consistent with 27 Al NMR observations by Stebbins et al (2003).…”
Section: Geochemical Perspectives Letters Lettermentioning
confidence: 99%
“…The oxygen vacancy substitution, one of the most likely mechanisms, in aluminous bridgmanite may provide suitable storage sites to incorporate water in the shallower part of the lower mantle (e.g., Navrotsky, 1999;Brodholt, 2000) according to the following reaction: 2MgAlO 2.5 (Brg) + H 2 O (fluid) = 2MgHAlO 3 (Brg) Eq. 2…”
Section: Geochemical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Navrotsky et al [17] reported the possible incorporation of O-defects in perovskite in a composition with ∼ 10 mol% AlO1.5 along the MgSiO3-MgAlO2.5 join. According to theoretical calculations this could reduce the bulk modulus by at least 10% [9].…”
Section: Phase Relationsmentioning
confidence: 99%
“…Andrault et al [8] and Walter et al [14] have measured the compressibilities of a series of aluminous perovskites along the charge-coupled join, and observed only a mild effect on the bulk modulus generally consistent with theoretical calculations. Navrotsky et al [17] synthesized perovskites along the O-defect join, as well as other MgO-saturated perovskite compositions.…”
Section: Mgalo25 (O-defect Join)mentioning
confidence: 99%